Association of Mean Platelet Volume / Platelet Count Ratio with Clinical Severity and Infarct Volume in Patients with Acute Ischemic Stroke - Nayyar, Muhammad Wasi; Mahmood, Asad; Liaqat, Jahanzeb; Robert, Helen Mary; Mahmood, Rafia; Khurshid, Ayesha (Pakistan Armed Forces Medical Journal, 2023)
Objective: To examine the clinical severity and infarct volume of acute ischemic stroke (AIS) compared to control subjects by comparing the mean platelet volume/platelet count (MPV/PC) ratio.Study Design: Cross-sectional (validation) study.Place and Duration of Study: Acute Stroke Unit, Pak Emirates Military Hospital (PEMH), Rawalpindi, from Jul and Dec 2020.Methodology: This study included 50 consecutive AIS patients (Group-1) and 50 healthy subjects (Group-2). An automated haemanalyser determined MPV and MPV/PC ratios. In addition, a modified Rankin Scale for the severity of AIS and ABC/2 method for infarct volume was used.Results: This study comprised 69 males and 31 females. Statistical analysis showed that MPV and MPV/PC have significantly different mean values between Group-1 and Group-2 at a p-value of 0.001. In addition, according to the Rankin scale, a significant difference of means (p-value